Decreased Risk of Anxiety in Diabetic Patients Receiving Glucagon-like Peptide-1 Receptor Agonist: A Nationwide, Population-Based Cohort Study - Tsai, Wen-Hsuan; Sung, Fung-Chang; Chiu, Lu-Ting; Shih, Ying-Hsiu; Tsai, Ming-Chieh; Wu, Shu-I (Frontiers in Pharmacology, 2022)
Background Previous findings on using Glucagon-like peptide-1 receptor agonist (GLP1-RA) as an antidepressant were conflicting, lacking large-scale studies. We used population-based data to investigate depression and anxiety risk in diabetic patients receiving the medication. Methods From claims records of the National Health Insurance Research Database (NHIRD) of Taiwan, we identified cohorts of 10,690 GLP1-RA users and 42,766 propensity score-matched patients without GLP1-RA use from patients with diabetes mellitus (DM) diagnosed in 2011-2017, matched by age, gender, index year, occupation, urbanization, comorbidities, and medications. Incidence, hazard ratios (HR) and 95% confidence interval (CI) of depression and/or anxiety were estimated by the end of 2017. Results The overall combined incidence of anxiety and/or depression was lower in GLP1-RA users than in non-users (6.80 versus 9.36 per 1000 person-years), with an adjusted HR (aHR) of 0.8 (95% CI: 0.67-0.95) after controlling for covariates. The absolute incidence reduction was greater in anxiety (2.13 per 1000 person-years) than in depression (0.41 per 1000 person-years). The treatment effectiveness was significant for women. Patients taking GLP1-RA for longer than 180 days had the incidence of anxiety reduced to 2.93 per 1000 person-years, with an aHR of 0.41 (95%CI: 0.27-0.61), compared to non-users. Dulaglutide could significantly decrease risks of both anxiety and depression. Conclusions Patients with DM receiving GLP1-RA therapy have a greater reduction of the risk of anxiety than that of depression. Our findings strengthen previous research that advocated possible anti-depressant or anxiolytic effects of GLP1-RA and may lead to improved treatment adherence among patients with DM.